Outcome of tectonic graft in corneal perforations - Mengal, Mahtab; Waseem, Madiha (Journal of Liaquat University of Medical & Health Sciences, 2021)
OBJECTIVE: To evaluate the anatomical outcome of tectonic graft in corneal perforations. METHODOLOGY: This Prospective, interventional study was conducted at the Ophthalmology department, Helpers Teaching Eye Hospital, Quetta from February 2019 to March 2020. Fifty Two eyes of 50 subjects, aged between 5 to 80 years, either gender, with corneal perforation (<4mm), traumatic, inflammatory, spontaneous, and infectious perforations were included. Data analysis was done on SPSS version 23. A Chi-square test was applied. A P-value of ? 0.05 was considered significant. RESULTS: 35 (70%) were males and 15 (30%) were females. The mean age was 41.68 ± 19.25 years (range: 5 years to 80 years). The site of perforation was paracentral in 26 (52%), peripheral in 15 (30%), limbal in 6 (12%), and central in 3 (6%) patients. The most common indication for tectonic graft was infectious keratitis in 23 (46%) patients followed by trauma in 17 (34%), inflammatory causes in 6 (12%), and spontaneous in 4 (8%) patients. Postoperative complications include peripheral anterior synechiae in 10 (20%), phthisis bulbi in 4 (8%), endophthalmitis in 2 (4%), persistent leakage, and loose corneal sutures in 2 (4%), and recurrence of infection in 1(2%) cases. The anatomical success of the graft was achieved in 44 (88%). No significant change in anatomical outcome was observed concerning age group (P=0.329), gender (P=0.849), and indications for tectonic graft (P=0.593). CONCLUSION: Tectonic graft is useful for therapeutic management of corneal perforations as it restores the globe's integrity. KEYWORDS: Tectonic graft, Corneal Perforations, Anatomical integrity